Improving Mathematics Learning Outcomes of Third-Grade Students on the Material of Calculating the Perimeter and Area of Flat Buildings through the STAD Type Cooperative Learning Model - Rosfiani, Okta; Marwiyah, Marwiyah; Saputra, Levi Elo; Kamil, Moh Nizham; Al-Fajry, Moh Faiz (Journal of Education Method and Learning Strategy, 2024)
Based on the learning results of class V students at SDS Islam An Nuriyah in South Jakarta, it shows that the results of learning Indonesian about writing summaries of the contents of children's books/stories are still below the specified KKM, namely 75. Of the 35 students, only 13 were able to reach the KKM. Therefore, improvements were made to Indonesian language learning regarding writing summaries of the contents of children's books/stories using the Jigsaw type Cooperative Learning method. This research method uses a cycle system consisting of planning, implementation, observation and reflection. This research aims to improve learning and achieve the expected results. To improve student learning outcomes in writing summaries of the contents of children's books/stories, a Jigsaw type Cooperative Learning method solution is offered. The results of the research show that learning mastery in each cycle has increased using this method. In the pre-cycle, there were only 13 students whose learning completeness was above the KKM 75 out of 35 students (40.00%). In cycle 1 it increases to 19 people (54.29%). Meanwhile in cycle 2 it increased to 28 people (80.00%). The results of this research can improve learning outcomes. This research can be concluded that the Jigsaw type Cooperative Learning method can improve the learning outcomes of class V students at SDS Islam An Nuriyah in Indonesian language lessons on writing summaries of the contents of children's books/stories.